PERAN PEMERINTAH DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BAITUL MAL DI ACEH - Azhari, Riski; Nurdin, Abidin; Alqarni, Wais (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
This study discusses the role of government in community economic empowerment through Baitul Mal in Aceh. This study aims to contribute to the government on social issues such as poverty and underdevelopment. The method used in this study is qualitative research with data collection techniques, namely the study of literature. While the theory used is structural functionalism theory. Research findings from the discussion and analysis above that the Government of Aceh through Baitul Mal has played a role in empowering the economic community in Aceh in the form of productive Zakat, Infaq and Shadaqah. The government through Baitul Mal has carried out programs (a) providing business capital to the people who have their businesses to develop their businesses, both in the agriculture, animal husbandry, industrial, and trade sectors, (b) providing assistance in working tools, in the form of motorized pedicabs, and the tools needed in the agriculture, animal husbandry, trading, and industrial sectors that support their businesses, and (c) human resource development through skills training and skills to the community. This community economic empowerment program clearly contributes to social problems such as poverty, under development and access to education.